The Influence of Occupational Safety and Health Culture on Workforce Sustainability through Employee Engagement - Mubarok, Ichsan Syachrul; Anna Suzana (Jurnal Manajemen, 2026)
This study examines the effect of occupational safety and health (OSH) culture on workforce sustainability, with employee involvement as a mediating variable at SPPBE Adam Pramudya. Preliminary findings indicate the presence of occupational risks and varying levels of employee involvement that may affect workforce sustainability, highlighting the need for an OSH culture that encourages active employee participation. This research adopts a quantitative approach using a survey of 100 employees. Data were collected through a structured questionnaire that met validity and reliability requirements and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that OSH culture has a positive and significant effect on employee involvement and workforce sustainability. Employee involvement also significantly influences workforce sustainability and mediates the relationship between OSH culture and workforce sustainability. These findings emphasize the importance of strengthening OSH culture through enhanced employee involvement to ensure sustainable workforce management.